2020
DOI: 10.3390/vaccines8040560
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinations and Chronic Diseases: Knowledge, Attitudes, and Self-Reported Adherence among Patients in Italy

Abstract: The aims of this cross-sectional survey were to evaluate the knowledge, attitudes, and self-reported adherence to recommended vaccinations among a random sample of patients with chronic conditions presenting for a medical visit in out-patient clinics in Italy. Patients who were healthcare workers (HCWs), those with diabetes, those who had received information by Internet, physicians, and friends/relatives, and those who needed more information were more likely to know that the influenza vaccine is recommended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 37 publications
5
18
0
4
Order By: Relevance
“…They were less willing to take a vaccine than other respondent groups [ 48 ]. A population-based study conducted in Germany found that people with chronic diseases were not vaccinated against flu due to mistrust of the vaccination and low perception of the disease’s risk [ 49 ]. This has serious implication as adverse consequences of COVID-19 is prevailing among individual with chronic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…They were less willing to take a vaccine than other respondent groups [ 48 ]. A population-based study conducted in Germany found that people with chronic diseases were not vaccinated against flu due to mistrust of the vaccination and low perception of the disease’s risk [ 49 ]. This has serious implication as adverse consequences of COVID-19 is prevailing among individual with chronic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, vaccine uptake rates reported in previous studies among patients with chronic conditions have varied. In a study conducted among patients with chronic diseases visiting an Italian out-patient clinic, Napolitano et al found that nearly half of participants were vaccinated against influenza in 2018–2019 [ 22 ]. However, Ye et al and Mohr et al, [ 23 , 24 ] reported that only 7.8% of diabetic patients in china and less than 30% of patients with chronic pulmonary diseases in Germany received influenza vaccine respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Students who had any chronic condition were more skeptical toward vaccines. This aspect is not explored much in previous studies, but in one recent study, while the majority of people with chronic disorders had a positive attitude toward vaccination, vaccination among those people was lower [21]. Interestingly, this study discovered students consuming healthy food were more inclined to maintain regular hand hygiene and practice safe sex behavior.…”
Section: Variablesmentioning
confidence: 57%